THE EFFECTIVENESYS OF EDUCATION USING TOUGH FAMILY MODEL AS A MAIN FACTOR OF MENTAL HEALTH DURING COVID-19 PANDEMIC - Liyanovitasari Liyanovitasari; Puji Lestari (Jurnal Keperawatan dan Kesehatan Masyarakat Cendekia Utama, 2023)
COVID-19 has changed people's way of life and forces everyone to adapt to the situation. Many restrictions on activity and mobility cause people to spend more time at home to work or study. The pandemic also makes many people to be terminated from job or called as PHK. Family support is really needed in this situation. A family should be able to be tough to face stress and crisis effectively. The aim of this research is to know the effectiveness of education using tough family model as a main support of mental health during Covid-19 pandemic.This research used quantitative approach. The design used quasi experiment of pre-experimental design of one group pretest-posttest design. The respondents were 50 cadres by filling in a questionnaire in pre and post-test stage and they got education of tough family model as the intervention of this research. The intervention was given directly to measure the knowledge and ability of the families in maintaining mental health. Data analysis used dependent t-test to know the differences of knowledge and ability of the families in maintaining mental health before and after they got education using tough family model.The results of this research showed the knowledge of the cadres before getting the education of tough family model as many as 1.44% and after the education it increased to 2.84%. The ability of the families in maintaining mental health before getting the education was 1.72% and increased to 2.52% after the education. There were some differences of knowledge and ability of the families in maintaining mental health before and after getting the education showed by p value as many as 0.000.This research expects the cadres to be able to apply tough family model in taking care of the members of the family in order to maintain mental health. Keywords: Education Model, Tough Family, Mental Health.